Hydrodynamics affected by submerged vegetation with different flexibility under unidirectional flow - Wu, Chenhui; Wu, Shiqiang; Wu, Xiufeng; Zhang, Yu; Feng, Kedong; Zhang, Weile; Zhao, Yuhang (Frontiers in Marine Science, 2023)
Submerged vegetation has changed the hydrodynamic characteristics of rivers, lakes, wetlands and coastal zones. However, few studies have focused on the effect of flexible submerged vegetation on hydrodynamic characteristics under unidirectional flow. Therefore, laboratory experiments are used to study the effects of submerged vegetation with different flexibility on the flow structure and turbulence characteristics under unidirectional flow. The results show that the reconfiguration and coordinated waving motion of the flexible submerged vegetation redistribute the flow velocity, Reynolds stress and turbulent kinetic energy inside and outside the vegetation canopy. With the gradual decrease of the deflection height of vegetation, the dimensionless velocity difference, dimensionless mixed layer thickness, bulk drag coefficient, vegetation canopy averaged turbulent kinetic energy and the vegetation canopy averaged contribution rate of shear production term of turbulent kinetic energy also decrease, while the trend of the penetration depth of Reynolds stress is opposite. Based on the turbulent kinetic energy budget equation, a TKE model that can be used to predict the shear production term of turbulent kinetic energy and the turbulent kinetic energy within the vegetation canopy is established, where the scaling factor is determined by the vegetation canopy Cauchy number. The TKE model can predict the vegetation canopy averaged turbulent kinetic energy and local turbulent kinetic energy within the vegetation canopy under unidirectional flow containing submerged vegetation with different flexibility with high accuracy and can be used as a simple method to predict vegetation-induced turbulence and the sediment and material transport characteristics under the influence of submerged vegetation with different flexibility.